2006
DOI: 10.1051/0004-6361:20053988
|View full text |Cite
|
Sign up to set email alerts
|

Induced two-photon decay of the 2s level and the rate of cosmological hydrogen recombination

Abstract: Induced emission due to the presence of soft CMB photons slightly increases the two-photon decay rate of the 2s level of hydrogen defining the rate of cosmological recombination. This correspondingly changes the degree of ionization, the visibility function and the resulting primordial temperature anisotropies and polarization of the CMB on the percent level. These changes exceed the precision of the widely used Cmbfast and Camb codes by more than one order of magnitude and can be easily taken into account.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
153
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 17 publications
8
153
0
Order By: Relevance
“…For the 2s-1s two-photon process, this behavior was also seen earlier (Chluba & Sunyaev 2006b). In the case of 3s and 3d twophoton decays, this enhances the emission of photons close to the Lyman β resonance (cf.…”
Section: Appendix C: Computation Of Two-photon Profilessupporting
confidence: 77%
See 1 more Smart Citation
“…For the 2s-1s two-photon process, this behavior was also seen earlier (Chluba & Sunyaev 2006b). In the case of 3s and 3d twophoton decays, this enhances the emission of photons close to the Lyman β resonance (cf.…”
Section: Appendix C: Computation Of Two-photon Profilessupporting
confidence: 77%
“…After the seminal works of Zeldovich et al (1968) and Peebles (1968) on cosmological recombination, and the later improvements to the theoretical modeling of this epoch (e.g., Jones & Wyse 1985;Seager et al 2000), leading to the widely used standard recombination code Recfast (Seager et al 1999), over the past few years the detailed physics of cosmological recombination has again been reconsidered by several independent groups (e.g., Dubrovich & Grachev 2005;Chluba & Sunyaev 2006b;Kholupenko & Ivanchik 2006;Rubiño-Martín et al 2006;Switzer & Hirata 2008;Wong & Scott 2007). It is clear that understanding the cosmological ionization history at the level of ∼0.1% (e.g., see Fendt et al 2009, for a more detailed overview of the different previously neglected physical processes that are important at this level of accuracy) will be very important to accurate theoretical predictions of the cosmic microwave background (CMB) temperature and polarization angular fluctuations (e.g., see Hu et al 1995;Seljak et al 2003) to be measured by the Planck Surveyor 1 , which will be launched later this year.…”
Section: Introductionmentioning
confidence: 99%
“…Important corrections include feedback from higher-order lines [16,17], time-dependent effects in Ly-α [18], and frequency diffusion due to resonant scattering [19][20][21]. An accurate 2s − 1s two-photon decay rate also requires following the radiation field to account for stimulated decays [22] and absorption of non-thermal photons [23,24]. Dubrovich & Grachev [25] suggested that two-photon transitions from higher levels may have a significant effect on the recombination history.…”
Section: Introductionmentioning
confidence: 99%
“…see Fendt et al 2008, for detailed overview), including subtle physical processes during hydrogen (e.g. see Dubrovich & Grachev 2005;Chluba & Sunyaev 2006b;Kholupenko & Ivanchik 2006;Rubiño-Martín et al 2006;Hirata 2008) and helium recombination (e.g. see Switzer & Hirata 2008a,b;Hirata & Switzer 2008;Kholupenko et al 2007;Wong & Scott 2007;Rubiño-Martín et al 2008;Kholupenko et al 2008).…”
Section: Introductionmentioning
confidence: 99%